Measuring the recycling potential of rare earth dysprosium in China - Ruohua, LIU; Xianlai, ZENG (Zi yuan ke xue, 2025)
[Objective] Secondary resources from “urban minerals” play an increasingly significant role in the sustainable supply of resources. Dysprosium is an important rare earth element widely used in products such as household appliances, automobiles, and wind turbines. Accurately assessing the recycling potential of dysprosium is an urgent scientific issue that needs to be addressed. [Methods] This study used a bottom-up approach to calculate the consumption of dysprosium in China from 2001 to 2023. The consumption and scrap conditions of dysprosium from 2024 to 2050 were predicted to assess the recycling potential of dysprosium from “urban minerals”. [Results] (1) The consumption of dysprosium increased rapidly from 2001 to 2023, primarily being applied in wind turbines, electric vehicles, and air conditioners. (2) From 2024 to 2050, dysprosium consumption in household appliances, automobiles, and e-bikes would first increase and then decline, while consumption in wind turbines would continue to rise. (3) Dysprosium consumption would peak at about 7200 t by 2042, then remain relatively stable at about 6600 t between 2041 and 2050, mainly concentrated in electric vehicles and wind turbines. (4) With the increase of product scrap, the recycling potential of dysprosium would continuously rise, reaching about 6500 t by 2050, which is expected to meet the future demand. [Conclusion] Although China ranks among the world’s top holders of dysprosium reserves, the current mining volume is unlikely to meet future product demand. Therefore, it is necessary to develop a circular economy and recycle dysprosium from “urban minerals” to fill the demand gap, reduce the pressure on primary mineral extraction, and ensure the security of dysprosium resource supply.